Small mammals reduce distance dependence and increase seed predation risk in tropical rainforest fragments. (29th June 2022) - Krishnan, Aparna; Osuri, Anand M.; Krishnadas, Meghna
Abstract: Seed predation and reduced predation risk with distance from conspecific trees are important influences on tree regeneration in tropical forests. Shifts in animal communities, such as an increase in rodents and other small mammals due to forest fragmentation, could alter patterns of seed predation and affect tree regeneration and community dynamics in forest fragments. We performed a field experiment on four native rainforest tree species in the Western Ghats, India, to test whether fragmentation increases seed predation by mammals and alters the distance dependence of seed predation. We monitored seed predation within open and mammal exclosure plots, near and far from the canopies of conspecific trees, in contiguous and fragmented forests. Seed predation of Cullenia exarillata, Ormosia travancorica, and Syzygium rubicundum was markedly higher in forest fragments, and more so within open plots than exclosures, while the predominantly insect‐predated Acronychia pedunculata experienced similar predation in contiguous forests and fragments. Seed predation of C. exarillata and S. rubicundum was unrelated to distance from conspecific trees in open plots in both contiguous forests and fragments, in contrast to exclosures that showed marked near versus far differences in seed predation. Our findings suggest that by increasing overall seed predation risk and imposing similar seed predation risk near and far from adults variably across the tree species, small mammals could alter processes that shape tree diversity and species composition in fragmented tropical rainforests. Abstract : Fragmentation of forests can shift animal assemblages towards an increase in small mammals such as rodents and consequently alter patterns of seed predation. Our field experiment in fragmented and contiguous forests in the Western Ghats, India, showed that small mammals markedly increased seed predation risk and reduced distance‐dependence of seed predation in forest fragments. The results suggest that greater small mammal predation could reduce the availability of safe sites for plant recruitment in forest fragments.